O HTPC específico de professores de Educação Física: contribuições para a prática educativa na pré-escola - Oliveira, Natália da Silva de (2021)
Historically, Physical Education seeks its space as a curricular component, and in Children Education there is no mandatory professional of the area (or specialist), leaving this choice to the discretion of each education system. In this sense, the present work is circumscribed within the scope of the teaching of Physical Education teachers who work in Children's Education, more specifically in pre-school, and its purpose is to investigate the continuing education of these teachers through the Hour of Collective Pedagogical Work (HTPC), specific for Physical Education teachers held in a city in the interior of the State of São Paulo. The question is to what extent the specific HTPC for Physical Education teachers contributed/contributes to the educational practice of these teachers who work in early childhood education? In view of such questioning, this research aims to understand if and how the Collective Pedagogical Work Schedule (HTPC) influences/influenced the educational practice of Physical Education teachers working in pre-school. The theoretical framework was built addressing the continuing education of teachers, as well as the conceptions and history of the HTPC and Physical Education in Kindergarten. For this, the research was based on the qualitative approach, having as subjects five Physical Education teachers who work with preschool children and participated in the specific HTPC for Physical Education teachers. In the instance of data collection, semi structured interviews were conducted with five Physical Education teachers, in order to contemplate the research objectives. The data analysis was performed based on Content Analysis. It was identified that the teachers who had been working for a longer time had an easier time organizing and working with children. The teachers pointed out some remarkable characteristics about the organization of the specific HTPC, such as the exchange of experiences in the form of narratives and presentation of videos and activities by the pedagogical coordinator. They recognized in the exchange of experiences a factor by which the specific HTPC was characterized as a moment of continuing education. Among the implications listed that this moment provided to the educational practice, the widening of the repertoire of activities and the perception of different forms of mediation and work with children were signaled, on a larger scale by the subjects. We emphasize that the Physical Education teachers do not reject the HTPC held in a school with a larger number of classes, with regular teachers and management, however, they consider that this moment is mostly focused on the continuing education of regular teachers. The proposals of this study go towards the valorization and return of the specific HTPC (expressed in the teachers' statements).